Answer:
[tex]\left(\; \boxed{1}\:,\boxed{-1}\;\right)\; \textsf{and}\;\left(\; \boxed{7}\:,\boxed{-1}\;\right)[/tex]
Step-by-step explanation:
Given system of conics:
[tex]\begin{cases}(x-4)^2+(y+1)^2=9\\\\\dfrac{(x-4)^2}{9}+\dfrac{(y+1)^2}{81}=1\end{aligned}[/tex]
Multiply the second equation by 81:
[tex]\implies \dfrac{81(x-4)^2}{9}+\dfrac{81(y+1)^2}{81}=81[/tex]
[tex]\implies 9(x-4)^2+(y+1)^2=81[/tex]
Rearrange to make (y + 1)² the subject:
[tex]\implies (y+1)^2=81-9(x-4)^2[/tex]
Substitute into the first equation and simplify:
[tex]\implies (x-4)^2+81-9(x-4)^2=9[/tex]
[tex]\implies -8(x-4)^2=-72[/tex]
[tex]\implies (x-4)^2=9[/tex]
Solve for x:
[tex]\implies \sqrt{ (x-4)^2}=\sqrt{9}[/tex]
[tex]\implies x-4=\pm3[/tex]
[tex]\implies x=4\pm3[/tex]
[tex]\implies x=1, 7[/tex]
Substitute the found values of x into the first equation and solve for y:
[tex]\begin{aligned}x=1 \implies (1-4)^2+(y+1)^2&=9\\(-3)^2+(y+1)^2&=9\\9+(y+1)^2&=9\\(y+1)^2&=0\\y+1&=0\\y&=-1\end{aligned}[/tex]
[tex]\begin{aligned}x=7 \implies (7-4)^2+(y+1)^2&=9\\(3)^2+(y+1)^2&=9\\9+(y+1)^2&=9\\(y+1)^2&=0\\y+1&=0\\y&=-1\end{aligned}[/tex]
Therefore, the solution to the given system of conics is: